Fungicidas de efeitos fisiológicos no metabolismo e desenvolvimento de plantas de melão rendilhado sob cultivo protegido - Macedo, Ana Claudia [UNESP] (2015)
Fungicides until recently were used exclusively for Disease Control, however observations of physiological effects brought a new concept for the use of these products. The physiological effects evidenced lately have shown that the fungicides positively influence the metabolism of plants acting in gas exchange, respiration process, the activity of antioxidant enzymes, nitrate reductase, in hormones and this resulting in higher or better fruit production. This study aimed to evaluate the effect of the application of azoxystrobin, boscalida, pyraclostrobin and fluxapyroxad in net melon plants (Cucumis melo var. Reticulatus) in greenhouse conditions, aiming its physiological effects on metabolism and plant development and as improvement in production and fruit quality. The experiment has been conducted in an experimental field of the Faculty of Agricultural Sciences at the Universidade Estadual Paulista, Botucatu-SP in a protected environment. The experimental design was a randomized block with seven treatments: one control and six fungicide applications: azoxystrobin 60 g ha-1, boscalida 75g ha-1, pyraclostrobin 50 g ha-1; boscalida (37,5g ha-1) + pyraclostrobin (25 g ha -1); fluxapyroxad 75g ha-1and fluxapyroxad (50,1g ha-1) + pyraclostrobin (99,9g ha-1) applied 14 days after sowing and the remainder of the application interval of 7 days foliar. The effect of the treatments was assessed through observations of the following: CO2 assimilation rate, transpiration rate, water use efficiency, carboxylation efficiency, chlorophyll a fluorescence, SPAD index, quantification of chlorophyll a and b in lipid peroxidation, the activity of nitrate reductase, peroxidase, catalase and superoxide dismutase (SOD) and post harvest the fruits of net melon. Based on obtained results it was concluded that the fungicides have positive ...